1, 3‐Diamine‐Derived Bifunctional Organocatalyst Prepared from Camphor. Issue 23 (9th November 2016) - Ričko, Sebastijan; Svete, Jurij; Štefane, Bogdan; Perdih, Andrej; Golobič, Amalija; Meden, Anže; Grošelj, Uroš
Abstract: Chiral 1, 2‐diamines are privileged structural motifs in organocatalysis, whereas efficient 1, 3‐diamine‐derived organocatalysts are very rare. Herein we report a highly efficient camphor‐1, 3‐diamine‐derived squaramide organocatalyst. Its catalytic activity in Michael additions of 1, 3‐dicarbonyl nucleophiles to trans ‐β‐nitrostyrene derivatives provides excellent enantioselectivities (up to >99% ee ). Abstract :